2021
DOI: 10.3390/su13095036
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Circular Business Model Innovation through Keywords Analysis

Abstract: Ongoing economic, social and environmental developments have forced the production system to undertake a profound transformation, shifting from a linear to a circular model. The transformation towards a circular economy poses significant challenges for established companies, in many cases requiring a strong modification of their current business models, start-ups and new ventures. Firms need to completely rethink their value proposition, modifying how the product or service is produced, delivered to the custom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 82 publications
0
46
0
Order By: Relevance
“…This study offers a theoretical contribution by connecting the research streams of OI and CE and by adding new insights to the CE research. Previous studies have often indicated the importance of involving external stakeholders in circular innovation [17,19], but they scarcely discuss OCI in detail [41]. This research provides three new insights to the CE literature: first, it gives a comprehensive overview of the current status quo of circular innovation and its influencing factors.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This study offers a theoretical contribution by connecting the research streams of OI and CE and by adding new insights to the CE research. Previous studies have often indicated the importance of involving external stakeholders in circular innovation [17,19], but they scarcely discuss OCI in detail [41]. This research provides three new insights to the CE literature: first, it gives a comprehensive overview of the current status quo of circular innovation and its influencing factors.…”
Section: Discussionmentioning
confidence: 86%
“…CE literature points at the importance of applying open innovation approaches in circular innovation [17,18] but neither provides a model for OCI nor discusses the characteristics of OCI in detail. Various authors acknowledge the significance of multiple stakeholder engagement in circular innovation management [17][18][19]. To develop circular solutions, they propose co-creations with the supply chain, especially customers, suppliers, and distributors [17,[36][37][38]85].…”
Section: Open Innovation Approaches For a Circular Economymentioning
confidence: 99%
See 1 more Smart Citation
“…Further CE models and indicative examples are detailed in [3]. The survey in [5] examines the maturity of the most recent proposals (during 2019-2020). The enhanced collaborations between the involved entities in a CE lifecycle is considered of great importance, both for businesses that want to make the transition to circular operational models as well as for start-ups that are building their circular model from scratch [5].…”
Section: Introductionmentioning
confidence: 99%
“…The transformation of the traditional market into a service-oriented setting is now a fact. The integration of CE and IoT further promotes such data-driven service-oriented architectures (SoA) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%